Exploring green bond market systems in Nigeria and South Africa - Skirving, Ryan (Graduate School of Business (GSB), 2026)
The green bond (“GB”) market has emerged as a promising mechanism for mobilising capital towards sustainable and climate-resilient infrastructure projects. However, despite global growth in GB adoption, the take up of GBs in African markets remains low. This dissertation explores the green bond market systems (“GBMSs”) of South Africa and Nigeria using the Modified Jain Framework to evaluate and compare their respective market structures. The strengths, weaknesses, and opportunities for improvement of the two GBMSs were evaluated on five key metrics, namely: local bond market; policy guidelines and government support; certification; public versus private participation; and GB diversification. The study employs a quantitative research approach and uses secondary data from Bloomberg and regulatory reports to analyse the identified criteria. The findings indicate that South Africa's GBMS is relatively more developed, scoring 13 out of 15 in the analysis, supported by a deep and liquid local bond market, a well-defined regulatory framework aligned with international standards, and relatively significant private sector involvement. In contrast, Nigeria's GBMS, while benefiting from a degree of government support, faces structural challenges such as limited market liquidity, weak certification practices, and a narrow issuer base, resulting in its score of 7 out of 15. The study identifies key policy and market interventions to enhance GB adoption in both countries, including increasing government participation, improving certification frameworks, introducing tax incentives, and expanding issuer diversity. This research provides a comparative analysis, offering insights for policymakers, investors, and stakeholders aiming to accelerate the growth of SA and Nigeria's GB markets.